Towards a bilipschitz invariant theory - Cahill, Jameson; Iverson, Joseph W.; Mixon, Dustin G. (Applied and computational harmonic analysis, 2024)
Consider the quotient of a Hilbert space by a subgroup of its automorphisms. We study whether this orbit space can be embedded into a Hilbert space by a bilipschitz map, and we identify constraints on such embeddings.